Analysis of the coverage on TV news. Case study of teachers’ strike in Spain and Peru - Morales Morante, Fernando (2014)
This article analyzes and compares the cultural and audiovisual features that determine the styles and informative treatment of similar news content, issued by two private means different country: Peru and Spain. The study was made using the protocol Fact Efficient Model Construction (MOCIAE) and detects a clear bias in favor of the government’s position in both countries. However, as in the Spanish case increased presence of formal elements of staging and multiperspective opinion, the Peruvian version is detected finds treatment and focus less textual and predominantly spectacular, based on the use of resources ambient sound and the violent actions of the protesters.